2021
DOI: 10.1007/s10142-021-00787-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory non-coding RNAs: a new frontier in regulation of plant biology

Abstract: Beyond the most crucial roles of RNA molecules as a messenger, ribosomal, and transfer RNAs, the regulatory role of many non-coding RNAs (ncRNAs) in plant biology has been recognized. ncRNAs act as riboregulators by recognizing specific nucleic acid targets through homologous sequence interactions to regulate plant growth, development, and stress responses. Regulatory ncRNAs, ranging from small to long ncRNAs (lncRNAs), exert their control over a vast array of biological processes. Based on the mode of biogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 147 publications
(189 reference statements)
0
33
0
5
Order By: Relevance
“…To estimate the initiation of miRNA expression and determine appropriate sampling time points for mRNA and miRNA expression profiling, we tested the dynamic responses of critical genes involved in small RNA biosynthesis at 3, 6, 12, 24, and 48 hpi ( Figure 1C ). RDR2 and RDR6 encoding RNA-dependent RNA polymerases, play central roles in 24-nt-long repeat-associated small RNAs (rasiRNAs) and small interfering RNAs (siRNAs) biosynthesis; DCL1 encoding Dicer-like (DCL) enzymes is critical in processing miRNAs, and AGO1d encoding the Argonaute (AGO) protein is responsible for the RNA-induced silencing complex (RISC) formation, which regulates expression of target mRNAs in aspects of plant biology; DCL4 and DCL2 function in producing siRNAs; AGO4 serves in the loading of rasiRNAs; and DRB1 encoding dsRNA-binding protein is a cofactor of DCL (Bhogireddy et al, 2021 ). All the above genes were significantly triggered by M. brunnea inoculation before 48 hpi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the initiation of miRNA expression and determine appropriate sampling time points for mRNA and miRNA expression profiling, we tested the dynamic responses of critical genes involved in small RNA biosynthesis at 3, 6, 12, 24, and 48 hpi ( Figure 1C ). RDR2 and RDR6 encoding RNA-dependent RNA polymerases, play central roles in 24-nt-long repeat-associated small RNAs (rasiRNAs) and small interfering RNAs (siRNAs) biosynthesis; DCL1 encoding Dicer-like (DCL) enzymes is critical in processing miRNAs, and AGO1d encoding the Argonaute (AGO) protein is responsible for the RNA-induced silencing complex (RISC) formation, which regulates expression of target mRNAs in aspects of plant biology; DCL4 and DCL2 function in producing siRNAs; AGO4 serves in the loading of rasiRNAs; and DRB1 encoding dsRNA-binding protein is a cofactor of DCL (Bhogireddy et al, 2021 ). All the above genes were significantly triggered by M. brunnea inoculation before 48 hpi.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) 21-24 nucleotides (nt) in size, which are small endogenous non-coding single-stranded RNAs synthesized by an RNA silencing system (Bhogireddy et al, 2021 ), play momentous roles in modulating the gene expression in the plant at the post-transcriptional level (Waterhouse and Hellens, 2015 ). An increasing number of reports have demonstrated that miRNAs regulate the growth, development, and stress responses in the plant by binding reverse complementary sequences and afterward bringing about the cleavage and/or translational inhibition of target mRNAs (Brant and Budak, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rise of sequencing technologies has also enabled more specific and focused plant-based studies of ncRNAs. A particular focus has been laid on the role of ncRNAs in plant immunity, development and stress response (e.g., abiotic factors) [ 192 , 193 ]. Sequencing has also facilitated the study of plants not commonly used in research, such as pistachio [ 194 ], sugar beet [ 195 ], and kiwifruit [ 196 ].…”
Section: Exploring the Ncrna Landscape Beyond Humansmentioning
confidence: 99%
“…In addition to genetic resistance, fungal genomics is crucial for fungicide development by identifying potential fungicide targets, their validation and mode of action, as demonstrated in several pathosystems [12]. For more than a decade, small RNAs have taken central stage in the area of genomics due to their versatile functions in gene regulation and metabolic pathways [13,14].…”
Section: Introductionmentioning
confidence: 99%